-3b-25=-2(1+4b)+7

Simple and best practice solution for -3b-25=-2(1+4b)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3b-25=-2(1+4b)+7 equation:


Simplifying
-3b + -25 = -2(1 + 4b) + 7

Reorder the terms:
-25 + -3b = -2(1 + 4b) + 7
-25 + -3b = (1 * -2 + 4b * -2) + 7
-25 + -3b = (-2 + -8b) + 7

Reorder the terms:
-25 + -3b = -2 + 7 + -8b

Combine like terms: -2 + 7 = 5
-25 + -3b = 5 + -8b

Solving
-25 + -3b = 5 + -8b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '8b' to each side of the equation.
-25 + -3b + 8b = 5 + -8b + 8b

Combine like terms: -3b + 8b = 5b
-25 + 5b = 5 + -8b + 8b

Combine like terms: -8b + 8b = 0
-25 + 5b = 5 + 0
-25 + 5b = 5

Add '25' to each side of the equation.
-25 + 25 + 5b = 5 + 25

Combine like terms: -25 + 25 = 0
0 + 5b = 5 + 25
5b = 5 + 25

Combine like terms: 5 + 25 = 30
5b = 30

Divide each side by '5'.
b = 6

Simplifying
b = 6

See similar equations:

| 30-11w+w^2=0 | | M=KV+KR | | 3x^1/2-2^1/2 | | 96+6y=-6y | | 19x=77 | | (5a^5/3b^6)^2 | | 9x+10=5x+8 | | e^6-8x=1188 | | 16x^2-x^4=0 | | h=-16t^2+33t+48 | | 2u-9=5(u+3) | | 3x+3y=60 | | 3sin^2(x)+2sin(x)-5=0 | | t+2*t+2=4 | | 3-3x=1-4x | | x^2-10=74 | | -1-(-3)=x | | 1-(-3)=x | | 2(3x+5)=26-(6-3x) | | 2b+3b-5=5 | | 4x-12x^2=256 | | 2.7x+45.8=13.2-13.6x | | sin(4x)=-cos(2x) | | y=0.90x+116 | | .05x+.09(3x+20000)=49480 | | .4xy-2=6 | | 7+17t-16t^2=0 | | 2=-4(-2)+2 | | 6x-3y=-2 | | 2x=-4(-2)+2 | | y-(-9)=8/9(x-3) | | 7x^2+37x-30= |

Equations solver categories